α-Glucosidase Inhibitory Activity of Cycloartane-Type Triterpenes Isolated from Indonesian Stingless Bee Propolis and Their Structure-Activity Relationship - Niken Pujirahayu; Debu Kumar Bhattacharjya; Toshisada Suzuki; Takeshi Katayama (MDPI AG, 2019)
This study reports on the antioxidant activity and α-glucosidase inhibitory activity of five cycloartane-type triterpenes isolated from Indonesian stingless bee (Tetragonula sapiens Cockerell) propolis and their structure−activity relationships. The structure of the triterpenes was determined to include mangiferolic acid (1), Cycloartenol (2), ambonic acid (3), mangiferonic acid (4), and ambolic acid (5). The inhibitory test results of all isolated triterpenes against α-glucosidase showed a high potential for inhibitory activity with an IC50 range between 2.46 and 10.72 µM. Among the compounds tested, mangiferonic acid (4) was the strongest α-glucosidase inhibitor with IC50 2.46 µM compared to the standard (−)-epicatechin (1991.1 µM), and also had antioxidant activities with IC50 values of 37.74 ± 6.55 µM. The study on the structure−activity relationships among the compounds showed that the ketone group at C-3 and the double bonds at C-24 and C-25 are needed to increase the α-glucosidase inhibitory activity. The carboxylic group at C-26 is also more important for increasing the inhibitory activity compared with the methyl group. This study provides an approach to help consider the structural requirements of cycloartane-type triterpenes from propolis as α-glucosidase inhibitors. An understanding of these requirements is deemed necessary to find a new type of α-glucosidase inhibitor from the cycloartane-type triterpenes or to improve those inhibitors that are known to help in the treatment of diabetes.